Indications for hospital admission, prevalence of vascular and non-vascular complications and comorbidities among patients with diabetes mellitus admitted to a medical unit in a tertiary care hospital, Sri Lanka - P. U. De Silva; G. Kodithuwakku; N. P. Imbulgoda; M. D. Samarawikkrama; D. Palagasingha; S. D. Nanayakkara; T. P. Weerarathna (Sri Lanka College of Internal Medicine, 2022)
Background: Hospital admissions with diabetes-related complications are on the rise in Sri Lanka. We aimed to study indications for hospital admissions and the prevalence of micro, macrovascular and non-vascular comorbidities in patients with diabetes mellitus admitted to a medical unit in a tertiary care hospital.   Methods: A hospital-based, cross-sectional study was carried out in Teaching Hospital Karapitiya over six months. Four hundred in-ward patients with diabetes were studied. Evidence of diabetes nephropathy, nonvascular co-morbidities and indication for admission were extracted from medical records using a pretested data extraction form. Screening for Diabetic peripheral neuropathy (DPN), and diabetic retinopathy (DR) were carried out using standard protocols.   Results: The highest number of admissions (142) were due to infections of which 52.8 % were females. One-third (33.8%) of the patients had previous admissions during the past year with a significant female preponderance (66%). DPN and DR were detected in 55.4% and 52.9% respectively with a significant proportion of them being females. Diabetic nephropathy was diagnosed in 27.9%. Nearly half (47.3%) of the sample was on treatment for hypertension and 39.4% were on statins. Evidence of previous myocardial infarction was significantly higher among the females compared to males (72.8% vs. 27. 2%).   Conclusions: Infections were the most frequent indication for hospital admission among diabetic patients. DPN and DR are significantly higher among females than males. Use of statins for dyslipidaemia is suboptimal among the admitted patients.